Methodological analyses for determining thermal requirements of grape varieties in Tandil, Argentina - Rodríguez, Luis Damián; Aguas, Laura; Hernandez, Gabriela; Laddaga, Juan (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2025)
This study evaluated the thermal demand of different grapevine varieties (Cabernet Franc, Merlot, Semillón, and Tannat) in Don Bosco, Tandil, Buenos Aires, Argentina. Phenology was evaluated during four productive cycles, identifying periods from budburst to flowering onset (BB-FO), flowering onset to veraison onset (FO-VO), and veraison onset to maturity (VO-M). The National Meteorological Service of Argentina provided daily maximum and minimum air temperatures. Six thermal sum methods were used: methods 1.1, 1.2, and 1.3 depended on base temperature for vine development (10°C); methods 2.1 and 2.2, considered base temperature and optimum temperature (25°C); and method 3, considered base, optimum, and threshold temperature (35°C). These methods were evaluated using the standard error of the thermal sum. Methods 2.2 and 3 best fit all four varieties, allowing adequate estimates of cumulative daily heat summation. Highlights: The thermal requirements of four grapevine varieties (Cabernet Franc, Merlot, Semillón, and Tannat) were evaluated in Tandil, Argentina, using different thermal accumulation methods. Methods that consider optimal temperatures and thresholds (methods 2.2 and 3) showed greater accuracy in estimating phenological stages. Tandil’s climate proved suitable for cultivating red grape varieties, highlighting the region’s viticultural potential. The study highlights the need for precise thermal models to optimize grape management under changing climate conditions.